Differential DNA methylation patterns in whole blood from ACPA-positive patients with DMARD-naïve rheumatoid arthritis at clinical disease onset - Svendsen, Anders Jørgen; Mengel-From, Jonas; Junker, Peter; Dalgård, Christine; Davey Smith, George; Relton, Caroline L.; Elliott, Hannah R.; Kyvik, Kirsten; Lindegaard, Hanne; Christensen, Anne Friesgaard; Tan, Qihua (Frontiers in Immunology, 2025)
ObjectiveEpigenetic DNA imprints are increasingly being recognized as co-drivers of disease in complex conditions. In this exploratory and hypothesis-generating epigenome-wide association study (EWAS), we investigated differential methylation patterns in peripheral blood leucocytes from patients with early untreated ACPA-positive rheumatoid arthritis (RA) versus controls.MethodsWhole blood DNA was isolated from 101 disease-modifying anti-rheumatic drug (DMARD)-naïve patients with recent clinical onset of ACPA-positive RA and 200 controls. DNA methylation was studied using the Illumina MethylationEPIC BeadChips (Illumina). We assessed our findings against previously reported differentially methylated DNA positions associated with RA including an EWAS on peripheral blood leucocytes from a similar Drop Nordic cohort.ResultsWe identified 16,583 CpG sites and 14 differentially methylated regions (DMRs) associated with RA. The most robust DMRs were in the gene body of LAMP1 and the TNSF14 GENE known as LIGHT. We identified three novel Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, the taste transduction pathway, the olfactory pathway, and the viral carcinogenesis pathway, which have not previously been associated with RA. We replicated 2,248 CpG sites reported earlier in an EWAS on peripheral blood leukocytes from RA patients of Scandinavian ancestry with incipient untreated ACPA-positive disease.ConclusionWe have detected a considerable number of epigenetic marks with potential relevance to the pathogenesis of RA. These findings may pave the way for the development of narrowly targeted new drugs and possibly assist to retrieve persons at particular risk of acquiring RA.